New Strait Times , 4 February 2009 - Sager Ahmad (The New Straits Times Press (M) Bhd, 2009)
In the second part of the series which began last week, Sager Ahmad takes a look at events during the 1941 Japanese invasion that led to the retreat of British troops to Singapore.